The language instinct : how the mind creates language - Pinker, Steven, 1954- (London : Penguin Books, 2007)
How do babies learn to speak? Why are there so many languages? Do we think in our mother tongue? Who decides what's correct English? How did language evolve? In this landmark book, Pinker explains the mysteries of language within a coherent theory- that language is an adaptation for communication. 'Dazzling . . . Pinker's big idea is that language is as innate to us as flying is to geese . . . Words can hardly do justice to the superlative range and liveliness of Pinker's investigations.'Independent 'Reading Steven Pinker's book is one of the biggest favours I've ever done my brain . . . exhilaratingly brilliant.'Richard Dawkins 'An extremely valuable book.'Noam Chomsky 'Brilliant.' Observer Now with a new afterword